Multifunctional Carbon Quantum Dots as Potential Theranostic Agents - Lemos Vilches, Martín; Lillo, Cristian R.; Montanari, Jorge (My University, 2022)
Introduction: Carbon nanomaterials constitute a research field of growing interest innanomedicine due to their fluorescent properties and stability. In particular, carbonquantum dots (CQD) also have low toxicity and high biocompatibility. CQD can beapplied for photothermal therapy, which consists of heat generation at specific siteswhen exposed to an external source of electromagnetic radiation with a specificfrequency. This is a promising approach to treat skin cancer, among other skindiseases. In parallel, CQD may also exhibit photodynamic activity, generatingreactive oxygen species (ROS). In both cases, the efficiency of the therapy willdepend on the structure, composition and size of the nanoparticle.Objective: To synthesize and characterize CQD from natural carbon sources aspotential biomarkers and photothermal / photodynamic agents for topical treatmentof skin cancer.Materials and methods: CQD were made from watermelon juice and dehydratedblueberries. Urea was added to some stocks as a nitrogen source. The synthesiswas carried out using a steel and teflon reactor, by a solvothermal oxidation at highpressures and temperatures.Optical properties of CQD were characterized by UV-Visible spectroscopy andstationary and time-resolved fluorescence.ROS generation was indirectly determined by oxygen consumption (for singletoxygen formation) on CQD suspensions irradiated with a 400 nm wavelength lightsource. Also superoxide anion radical detection was performed by Colestatenzymatic kit irradiated at 505 nm.Size and surface charge were studied by dynamic light scattering, zeta potential, andTEM.To evaluate photothermal activity, CQD suspensions were irradiated for 2 minuteswith an 800 nm laser (1 W/cm 2 ).Results: Spectra were obtained. Stocks with urea presented higher oxygenconsumption, while superoxide production was not detected. Irradiated CQDaqueous suspensions increased their temperature.Conclusions: These CQD show potential for theragnostic applications
Ponencia presentada en la 51.ª Reunião Anual de la SBBq y el 46.º Congresso Brasileiro de Biofísica. Águas de Lindóia, Brasil, septiembre de 2022.
Keywords: Ciencias médicas y de la salud::Biotecnología médica